CHANGES IN THE ADVOCACY SYSTEM IN TURKESTAN (20S OF XX CENTURY) - O.K. Jaynarov (Western European Studies, 2024)
The article describes the changes that took place in the activities of the legal profession in Turkestan after the establishment of Soviet power, based on a wide range of primary sources and historical literature. It analyzes the legal services provided by lawyers, their results, the establishment of local defense boards, and the legal documents adopted in the RSFSR and the Turkestan ASSR regarding the legal profession in the early 1920s. Despite the Soviet state's implementation of measures to establish the legal profession in Turkestan, its activities remained unsatisfactory during this period. It became apparent that although the foundations of the Soviet legal profession were laid by the Bolsheviks, the main cadres within it were justice officials from the imperial period. Moreover, the majority of defenders who began working under the Bolsheviks were representatives of various professions without any legal education or experience.
Keywords: Turkestan; People’s Commissariat of Justice; courts